Z-Score and Zavgren Models in Implementing Financial Distress Management in Cigarette Companies - Lisnawati Lisnawati; Mirnawati Mirnawati; Fahmi Sulaiman; Ruri Aditya Sari (Institute of Computer Science (IOCS), 2021)
Business competition between companies is getting tougher and the trend of the international economy is leading to global competition, thus requiring companies to have strong competitiveness to survive during the COVID-19 pandemic. Based on the results of the pre-study, it was found that at the National cigarette company there was an increase in assets from 2016 to 2017 causing an increase in profit, but the increase in profit was not significant. The purpose of this study was to determine the financial condition of cigarette companies using the Altman Z-score and Zavgren methods. The study consists of 2 stages, namely the calculation of financial distress in companies using the Z-score model and stage 2 for financial distress in companies using the Zavgren model. This research was conducted by taking data provided by the Indonesia Stock Exchange. The sample of this research is cigarette companies listed on the Indonesia Stock Exchange for the 2016 – 2018 period. Companies that are included in the healthy classification are PT. Gudang Garam, Tbk, PT. HM. Sampoerna, Tbk and PT, Wismilak Inti Makmur, Tbk because they have Z Scores of 4.449, 23.82, and 16.06, all of which have Z Scores above 2.9. The financial condition of cigarette companies listed on the Indonesia Stock Exchange (IDX) during the 2016 – 2018 period according to the Zavgren model can be categorized as Healthy because the Pi value is at the upper and lower thresholds. Sampoerna, Tbk and PT, Wismilak Inti Makmur, Tbk because they have Z Scores of 4.449, 23.82, and 16.06, all of which have Z Scores above 2.9. The financial condition of cigarette companies listed on the Indonesia Stock Exchange (IDX) during the 2016 – 2018 period according to the Zavgren model can be categorized as Healthy because the Pi value is at the upper and lower thresholds. Sampoerna, Tbk and PT, Wismilak Inti Makmur, Tbk because they have Z Scores of 4.449, 23.82, and 16.06, all of which have Z Scores above 2.9. The financial condition of cigarette companies listed on the Indonesia Stock Exchange (IDX) during the 2016 – 2018 period according to the Zavgren model can be categorized as Healthy because the Pi value is at the upper and lower thresholds.